MACROECONOMIC VARIABLES AS IMPETUS OF FOREIGN PORTFOLIO INVESTMENT IN NIGERIA - Tyoga, Mgbangun Samuel; Gambo, Nasamu; Ogedengbe, Frank Alaba (ShodhKosh: Journal of Visual and Performing Arts, 2026)
Nigeria has experienced fluctuating levels of foreign portfolio investment (FPI), raising concerns about the macroeconomic factors that influence its inflow and sustainability. This study investigates the impact of exchange rate, gross domestic product (GDP), and stock market returns on FPI in Nigeria, using quarterly time series data from 2000 to 2024. The study employs the Autoregressive Distributed Lag (ARDL) model to estimate both short-run and long-run relationships. In the long run, exchange rate (β = 0.312, p = 0.001), GDP (β = 0.144, p = 0.017), and stock market returns (β = 0.098, p = 0.000) were all found to have significant positive effects on FPI. In the short run, exchange rate (β = 0.125, p = 0.034), GDP (β = 0.089, p = 0.033), and stock market returns (β = 0.057, p = 0.001) remained significant, while the error correction term (ECM = -0.621, p < 0.001) indicated a strong speed of adjustment toward long-run equilibrium. The study concludes that sound macroeconomic fundamentals are essential for sustaining FPI. It recommends exchange rate stabilization through credible policy measures, growth-enhancing reforms to support GDP expansion, and increased transparency and efficiency in the capital market to boost investor confidence and attract long-term portfolio flows.